Venture Capital – Generator of Growth of SME Investment Activities - Dželetović, Milenko; Milošević, Marko R; Čičić, Sonja Z (Industrija, 2017)
The aim of the paper is to point out the importance and role of venture capital in creation of new values based on the knowledge economy. By reviewing relevant literature about venture capital, this paper presents the importance of the venture capital investments in innovative activities of SMEs that have an impact on economic growth. Pointing to the importance and quantifying the overall effects of venture capital investments, will be used the overview and trends in venture capital investments in the sectors of economy in Europe which generate a larger number of patents. According to data during the period of 2007 - 2015 will be defined venture capital investments and number of registered patents in the sectors of the knowledge economy. Empirical analysis indicated that the venture investments in the sectors of the knowledge economy generated more patents in those sectors. In addition, the paper analyzes the venture capital investment and innovation activities of SMEs, which are reflected in patent activities, where the result is a correlation between these activities in the European economies.